ANALISIS EFISIENSI DAN KUALITAS PELAYANAN RUMAH SAKIT UMUM DAERAH (RSUD) KABUPATEN LOMBOK BARAT - Yusi Faizathul Octavia; Hery Suprayitno (Valid: Jurnal Ilmiah, 2016)
Regional General Hospital (Hospital) is one of the organizations in the field of health services that reflect how much responsibility and authority of the local government in providing services to the public, so that the hospital in carrying out its activities should pay attention to efficiency and improve service quality. The level of efficiency and quality of service can be used as a tool for measuring hospital performance. It is necessary for the evaluation of the efficiency and quality of service which is very important to measure the performance of an organization to produce better public services. The measurement of efficiency and quality of hospital services is very important to do. Due to measuring the efficiency and quality of services provided can help the hospital management to determine its performance in providing services to patients / public. Thus, the management can determine the strategic policy of creating the repair of the budget use and improving the quality of services provided. To solve this problem, researchers used primary data and secondary data. Primary data is used to analyze the quality of service of the General Hospital of West Lombok, while the secondary data is used to measure the level of efficiency. The aim of this study was to find out how the West Lombok district hospital performance is measured on the efficient use of the budget and how to actually view or the public perception tehadap quality of services provided by the hospital. The results showed that the management of the West Lombok district hospitals is not good because the efficiency levels above 100 percent means that financial management is said to be very inefficient. While the results of research on the quality of services afforded views of the five dimensions based on patient responses are all classified as less good